Vzgojiteljice v prvih prekmurskih vrtcih (1886–1920) - Časar, Sindi (Studia Historica Slovenica, 2023)
The article deals with the presentation of the Hungarianisation of education in the Hungarian part of the monarchy. The focus is on the duality of private and state initiatives to regulate preschool education and the legalization of the compulsory Hungarian language. Particular attention is paid to the development of kindergartens in Prekmurje and the origin and role of female teachers. The latter come from different parts of Hungary and, by working in the border area, become the agents of the Hungarianisation of children “from a very young age”. Their integration into the established Hungarian kindergarten system and their links with Budapest involve them in various social roles in the local environment that promote and disseminate the Hungarian language. The First World War and the annexation of Prekmurje to the new state have an impact on their destinies.
Keywords: Hungarian teachers; Hungarianization; kindergartens; Lendava; madžarizacija; madžarske vzgojiteljice; Murska Sobota; predšolska vzgoja; Prekmurje; transition; vrtci; Zgodovina